Public Libraries in Norway Help Non-Western Immigrant Women to Integrate into Society - Oxborrow, Kathryn (Evidence Based Library and Information Practice, 2012)
Abstract Objectives – To discover the ways in which the public library was used by immigrant women, with a particular focus on the library as a meeting place. Design – Semi-structured qualitative interviews conducted in the participants’ native languages. Setting – Public libraries in Norway. Participants lived in one of two cities both with a population of approximately 40,000 and a somewhat lower number of immigrants than the national average. Subjects – Nine non-western women who had immigrated to Norway between 8 months and 17 years prior to the study. Three women were from Iran, Kurdistan and Afghanistan respectively. All identified themselves as public library users. Methods – Participants were interviewed in their native languages and the qualitative results were analyzed in accordance with the theoretical framework set out by the authors. The main areas of focus were the role of the library in the generation of social capital, and the library as a high intensive versus low intensive meeting place. Main Results – Participants used public libraries in various ways. In the initial stages of life in a new country they were used to observe and learn about the majority culture and language. They were also used as a safe place to openly grieve and provide comfort among close friends without fear of being seen by other fellow countrymen. Over time, participants came to use the library space in more traditional ways such as for information, social, and professional needs. The study also revealed that using public libraries built trust in the institution of libraries and librarians as employees. Conclusions – The public library plays a key role in the generation of social capital, both in terms of integrating into the majority culture through observation and spontaneous interactions (bridging social capital) and connecting with others from participants’ home cultures (bonding social capital) for example through the provision of social space and other links to home such as native language materials. The public library was used initially by participants as a high intensive meeting place, for meeting with friends and consoling one another. In time, however, the public library became a medium- to low-intensive meeting place, with participants engaging in library programmes or in spontaneous interactions with other library customers. Moreover, the study refutes the Swedish Library Association’s conclusion that library is used more often by immigrants that have lived in the country for long periods of time.